First Record of The Burrowing Goby Trypuchen vagina from Pangpang Bay, Indonesia - Sapto Andriyono; Endang Dewi Masithah; Heru Pramono; Suciyono Suciyono (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2019)
The burrowing goby, Trypauchen vagina, is recorded for the first time from the Pangpang Bay of Banyuwangi, Indonesia. Types of fish T. vagina is a type that has not published in Indonesia. This fish was caught using trap net in waters Pangpang Bay, which is an essential area in Banyuwangi, East Java. The description of the morphology and fish habitat conditions shows that the region has a diversity of fish resources that need attention. This goby fish has a local name as fish bedhul picek due to the sense of sight on these fish as if it does not work. Eyes covered by skin and socket head section was not found their eyeballs. The body of the specimens is elongate and reddish-pink in fresh specimens in coloration. There is no barbel on the chin. Cycloid scales are present on the whole body except for the head. Muncar people commonly consume T.vagina. This fish has been food sources in several regions but uncommon at several local markets in Indonesia. The T.vagina inhabit at Pangpang Bay as the bay, which has the high primary productivity of these waters due to sufficient nutrient support. Enrichment of nutrient comes from the run-off land and also the input of the number of fishing activity (embankment). An earlier report said that this fish found in waters Banyu Asin, Palembang, Sumatra, Indonesia. It also confirms that the fish found in this study are also living in a mud substrate that is reasonably smooth with right mangrove conditions around the bay, which close to Alas Purwo National Park.